2015
DOI: 10.1186/s13068-015-0202-6
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei meiosis generates segmentally aneuploid progeny with higher xylanase-producing capability

Abstract: BackgroundHypocrea jecorina is the sexual form of the industrial workhorse fungus Trichoderma reesei that secretes cellulases and hemicellulases to degrade lignocellulosic biomass into simple sugars, such as glucose and xylose. H. jecorina CBS999.97 is the only T. reesei wild isolate strain that is sexually competent in laboratory conditions. It undergoes a heterothallic reproductive cycle and generates CBS999.97(1-1) and CBS999.97(1-2) haploids with MAT1-1 and MAT1-2 mating-type loci, respectively. T. reesei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…The same pipeline was applied to the QM6a-derived strain Rut-C30, resulting in a genome scaffold in perfect agreement with previously identified chromosomal rearrangements between the two genomes [14, 15]. This result prompts us to put forward predictive karyotypes for several other T. reesei strains and to discuss the impact of such karyotypes on the emergence of segmental aneuploidy during crossing experiments [10]. …”
Section: Introductionsupporting
confidence: 53%
“…The same pipeline was applied to the QM6a-derived strain Rut-C30, resulting in a genome scaffold in perfect agreement with previously identified chromosomal rearrangements between the two genomes [14, 15]. This result prompts us to put forward predictive karyotypes for several other T. reesei strains and to discuss the impact of such karyotypes on the emergence of segmental aneuploidy during crossing experiments [10]. …”
Section: Introductionsupporting
confidence: 53%
“…For example, under cellulase-inducing conditions, the production of secreted β-glucosidase comprises only about 1% of the total T . reesei cellulase [14], indicating that the hydrolysis of cellobiose constitutes a rate-limiting step during the enzymatic processing of cellulose [15, 16]. Although commercial cellulase is available, many of the most well-known biomass- degrading fungi display low β-glucosidase (cellobiose) activity, thus the initial bioconversion of biomass to sugars remains a key bottleneck in the process of biofuel production.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in T. reesei (teleomorph Hypocrea jecorina), sexual development results in fertilized perithecia embedded in stromata containing decahexads with 16 ascospores per ascus (859). Recently, we showed that the 16 ascospores are generated by one round of meiosis followed by two rounds of postmeiotic mitosis (1108).…”
Section: Sexual Developmentmentioning
confidence: 99%